Simultaneous inference of haplotypes and alleles at a causal gene - Larribe, Fabrice; Dupont, Mathieu J.; Boucher, Gabrielle (Frontiers in Genetics, 2015)
We present a new methodology which jointly infers haplotypes and the causal alleles at a gene influencing a given trait. Often in human genetic studies, the available data consists of genotypes (series of genetic markers along the chromosomes) and a phenotype. However, for many genetic analyses, one needs haplotypes instead of genotypes. Our methodology is not only able to estimate haplotypes conditionally on the disease status, but is also able to infer the alleles at the unknown disease locus. Some applications of our methodology are in genetic mapping and in genetic counselling.